Primary Bone Diffuse Large B-Cell Lymphoma: A Case Series and Review of Literature - Ramkita, Nora; Murti, Krisna; Devi, SNA Ratna Sari; Dwiryanti, Rizky (http://dharmais.co.id/, 2025)
Introduction: Primary bone lymphoma (PBL) is an uncommon lymphoid cell neoplasm that appears as one or more bone lesions and does not appear in any lymph nodes or other places outside the lymph nodes. This type accounts for approximately 1% of all lymphomas and 7% of all cancerous primary bone tumors.Case Presentation: We collected two respective cases of primary bone lymphoma in the Department of Anatomic Pathology, Faculty of Medicine, Sriwijaya University, Dr. Mohammad Hoesin General Hospital, Palembang, Indonesia. Both cases were diffuse large B-cell lymphoma, non-germinal center subtype (DLBCL non-GCB), in individuals 48 and 18 years old, located in the right femur. The prognosis for both patients was poor due to the advanced stage, as well as the second patient's refusal of chemotherapy. Conclusion: These cases demonstrate the diagnostic and therapeutic challenges of primary bone diffuse large B-cell lymphoma, particularly the aggressive non-GCB subtype. Early recognition, accurate histopathological diagnosis, and prompt, multidisciplinary management are essential to improve prognosis, especially in advanced-stage presentations. Delay in treatment or refusal of therapy significantly worsens patient outcomes.